Associations between fish reproductive cycle and the dynamics of metazoan parasite infection - Simková, Andrea; Jarkovský, Jirí; Koubková, Bozena; Barus, Vlastimil; Prokes, Miroslav (Parasitology research, 2005)
The parasite fauna of the stone loach (Barbatula barbatula) was investigated monthly from May to December 2001. Four parasite species were recorded: Gyrodactylus spp. (Monogenea), Tylodelphys clavata (Digenea), Proteocephalus sagittus (Cestoda), and Raphidascaris acus (Nematoda). The changes in the seasonal dynamics of parasite infection were investigated throughout the 8 months. The potential effect of the reproductive investment of the host, measured by gonad mass and gonado-somatic index (GSI), on the parasite infection was tested against the prediction that, during periods of high reproductive investment (beginning of the breeding period or forming gonads after breeding), the fish are more susceptible to parasite infection. Differences between parasite loads between genders were also hypothesized. Seasonal differences in infection were observed for all parasite species studied. The values of GSI showed a pattern of energy accumulation in the pre-reproductive period and at the beginning of breeding, a decrease during breeding, and an increase in the post-breeding period. A similar pattern was observed for parasite abundance, a strong or weak increase in spring and/or autumn and a decrease during summer (July and August). Positive correlations between the abundance of Gyrodactylus spp. and R. acus and both gonad mass and GSI were found in females after eliminating the effect of fish weight. Our results suggest that stone loach females are more susceptible to parasite infection in periods of higher reproductive investment. The main factor determining the infection of T. clavata was fish size. The abundance of P. sagittus was positively correlated with GSI in the total fish sample with no detectable effect of sex or fish weight. The increase in cestode infection in spring supports the hypothesis that the parasite life cycle could by synchronized with the beginning of host reproduction, probably induced by increasing fish hormone levels in the spring.
Keywords: Body Size; Cypriniformes; Seasons; Reproduction; náchylnost k nemoci; velikost těla; mužské pohlaví; Helminthiasis, Animal; cizopasní červi; helmintózy zvířat; Parasite Egg Count; Nematoda; Gonads; Organ Size; gonády; velikost orgánu; ženské pohlaví; zvířata; nemoci ryb; počet parazitárních vajíček; Host-Parasite Interactions; Disease Susceptibility; Cestoda; interakce hostitele a parazita; hlístice; rozmnožování; Fish Diseases; Helminths; máloostní; Female; roční období; Male; Animals